A Study on the Mechanical Behaviors of Jute-polyester Composites. (2017) - Deb, Anindya; Das, Sumitesh; Mache, Ashok; Laishram, Rokesh
Abstract: In the present exposition, coupon specimens extracted from jute-polyester laminates fabricated by the hand layup method combined with compression molding are subjected to tensile, compression and flexural tests in a UTM. Next a novel hybrid jute-steel composite is studied under similar conditions. It is shown that the gap in tensile strengths in warp and weft directions found in plain jute laminates is perceptibly reduced in their hybrid jute counterparts. Also, hybrid jute laminates have substantive residual tensile strengths on reaching peak strengths as compared to plain jute-polyester composites which fail abruptly, i.e. in a brittle manner, on reaching peak strength. Additionally, hybrid jute composites displayed higher tensile modulus and flexural stiffness, and consistent compressive strength as compared to plain jute-polyester composite laminates. It is shown that improvement in moisture resistance is an additional advantage of hybrid jute laminates.